NILAI - NILAI CINTA TANAH AIR DALAM PERSPEKTIF AL-QUR’AN - M. Alifudin Ikhsan (Universitas Negeri Malang, 2017)
Abstract: Nasionalism is a feeling of pride and participate in having a certain territory. This feeling is manifested in a willingness to sacrifice to protect its territory from a variety of threats and threats. The importance of the love of this homeland makes it a natural human nature that has been born. However, the problematic nowadays is the specialization of the meaning of love the homeland in everyday life. The dichotomy of the rejection of the Ashobiyah Islamist movement towards the nation state is one of the proofs of narrowing the meaning of love of the homeland in society. The study of this subject reveals the concept or idea related to love of the homeland in terms of religion and nation. This is important to do in order to create a more contextual understanding of the phenomenon of understanding the problem of love homeland. This study is very important to do given the lack of deep study of exploration of the content of the Qur'an in solving social problems that occur today. His hope with the study of this topic can open the public insight about the concept of love homeland in the Qur'an. This research reveals the values of love of the homeland in the perspective of the Qur'anAbstrak: Cinta tanah air (hubb al wathan) merupakan perasaan bangga dan ikut memiliki sebuah wilayah tertentu. Perasaan ini diwujudkan dalam sikap rela berkorban untuk melindungi wilayahnya dari berbagai ganggungan dan ancaman. Pentingnya rasa cinta tanah air ini menjadikannya sebuah tabiat alamiah manusia yang dimiliki sejak lahir. Namun, yang menjadi problematika saat ini adalah spesialisasi makna cinta tanah air dalam kehidupan sehari-hari. Dikotomi penolakan gerakan Islam Ashobiyah terhadap paham negara bangsa (nation state) menjadi salah satu bukti penyempitan makna cinta tanah air di masyarakat. Kajian terhadap pokok bahasan ini mengungkapkan konsep atau gagasan terkait cinta tanah air yang ditinjau dari segi agama dan bangsa. Hal ini penting untuk dilakukan agar tercipta pemahaman yang lebih kontekstual terhadap fenomena problematika paham cinta tanah air. Penelitian ini sangat penting untuk dilakukan mengingat sedikitnya kajian yang mendalam terhadap eksplorasi kandungan Alquran dalam memecahkan problematika sosial yang terjadi saat ini. Harapannya dengan dikajinya topik ini dapat membuka wawasan masyarakat tentang konsep cinta tanah air dalam Alquran. Penelitian ini mengungkap nilai-nilai cinta tanah air dalam perspektif Alquran DOI : http://dx.doi.org/10.17977/um019v2i22017p108